The Effect of Tax Information Systems and Taxation Sanctions Towards Taxpayer Compliance with Cafe Owners of SME ( Small-Medium Enterprise) Taxes - Magfirah Diiznania Armin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
Taxes are among the highest income generated by the state originating from within the country. However, most taxpayers did not understand how and what the tax information system is like in Indonesia and how tax Sanctions are applied. So that in this case it tends to reduce taxpayer compliance. This study aims to determine the effect of tax information systems and tax sanctions on taxpayer compliance. This research method is quantitative research using primary data. Determination of the sample using purposive sampling. The sample in this study consisted of 26 respondents who owned cafes in the city of Palu. The analytical method used is descriptive and statistical analysis. The results of this study indicate that partially the tax information system has a positive and significant effect on taxpayer compliance. However, tax sanctions are positive but did not effect, that meaning tax sancations are not significant to taxpayer compliance, because they have a t-calculated value of less than 0,05 with a correlation value of 2,3% on taxpayer compliance.